IMPROVING PROBLEM SOLVING ABILITY THROUGH THE DISCOVERY LEARNING APPROACH ON STUDY OF SOCIAL SCIENCES - Sarifudin, Enceng; Koswara, Koko; Firdaus, Anugrah Ramadhan (COLLASE (Creative of Learning Students Elementary Education), 2018)
The condition of Implementation of teaching and learning at the level of schooling today is still colored by the emphasis on the knowledge aspect and still a little referring to the involvement of students in the learning process itself. In addition, Implementation of teaching and learning social science, conducted by teachers has not been able to foster learning culture among students. The research method used Elliott Model Class Action Research which consists of three cycles and in each cycle there are three actions. Data collection techniques use observation guides, interview guides, field notes, student worksheets, evaluation sheets, photo cameras. The result of the research shows that there is an increase of learning steps by using discovery learning. The statement is based on the result of learning the average value the results of individual tests, the average cycle I of 7.48, cycle II of 7.76 while the third cycle of 7.84.Based on these results, IPS learning using discovery learning approach of student learning activities and student learning outcomes on export and import topics increased after implemented learning using discovery learning approach.